Nutritional considerations for the child athlete - Bar-Or, O. (Canadian Journal of Applied Physiology, 2001)
While nutritional issues are similar for all athletes irrespective of age, children have several physiological characteristics that distinguish them from adults and require specific nutritional considerations. These age- or maturation-related differences include: a greater need for protein intake, to support growth; a greater need for calcium intake, to support bone accretion; a higher energy cost of activities that include walking and running; lower losses of sodium and chloride in sweat; and a greater thermoregulatory strain at any given level of hypohydration. This review will focus on three areas: (a) a higher metabolic cost of locomotion, its causes, and possible relevance to the calculation of daily energy requirements for young athletes; (b) the effect of carbohydrate (glucose, glucose plus fructose, or glucose plus sucrose) ingestion on children's aerobic performance, substrate utilization, and immune responses; and (c) involuntary dehydration during exercise in hot climate and the means for its prevention.